Gendered health impacts of industrial gold mining in northwestern Tanzania: perceptions of local communities. Issue 3 (4th May 2021) - Leuenberger, Andrea; Kihwele, Fadhila; Lyatuu, Isaac; Kengia, James T.; Farnham, Andrea; Winkler, Mirko S.; Merten, Sonja
ABSTRACT: Mining projects affect the health of surrounding communities by inducing environmental, economic, social and cultural changes in different population groups. Health impact assessment (HIA) offers an opportunity to manage these impacts. This paper aims to explore gender differences of impacts on the wider determinants of health as described by communities impacted by industrial gold mining and consider the implications for impact assessment. We conducted 24 gender-separated, participatory focus group discussions at three study sites in northwestern Tanzania. Participants reported on a broad range of impacts on the wider determinants of health. Based on a thematic analysis, we identified gendered health impacts on men and women; in addition, children and adolescent boys and girls emerged as differently affected subpopulation groups. Located in the theory of the 'triple role of women', we suggest that different gender needs should be addressed more explicitly by HIA. Increased use of mitigation measures that recognise and address impacts on women's engendered roles, and their health, through addressing women's strategic gender needs, would strengthen HIA as a tool towards sustainable development.